JOURNEYS OF SURVIVAL: KIDNEY TRANSPLANT STORIES FROM THE PHILIPPINES - Fernandez, Ramon Gabriel (Academic Journal of Psychology and Education (AJPE), 2024)
Organ donation and transplantation remain the best and most costeffective clinical approach for people in the terminal stage of organ failure. Given the growing numbers of incidences of patients treated for end-stage renal disease (ESRD) and the plummeting rate of kidney transplantation in the US and Southeast Asia, little is known about the understanding of the life stories of kidney organ transplant recipients, specifically in the Philippines. The present study aimed to provide a narrative study of the life stories of individuals who received kidney transplantation through either a live or deceased organ donor. By employing Dewey’s theory of experience, the shared stories of the transplant recipients yielded the following themes: carefree life, struggles before transplant, and psychological effects of the past; support system, journey to liminality, and positive outlook in life for the present stories; giving back, fatalistic view of life and sense of normalcy for the future aspirations or stories of the respondents. Kidney transplantation goes beyond the surgical process; it encompasses lifelong social and psychological transition and transformation for kidney transplant recipients.